Effect of triggering material, size, and casting direction on ASR expansion of cementitious materials. (1st February 2021) - Diab, S.H.; Soliman, A.M.; Nokken, M.R.
Highlights: The increased the Fused silcia replacement level, the increased the rate of expansion. Geometry of the concrete specimen has a crucial role on the rate of expansion. Casting direction and specimens size govern the expansion rate. Regardless the specimens geometry and volume, mass change followed the same trend of expansion. Abstract: Alkali-silica reaction (ASR) is considered one of the most critical internal damaging mechanisms for concrete. Several specifications and testing methods have been used to evaluate concrete performance, undergoing ASR damage. This had led to enormous data in the literature, yet some are contradictory. Hence, the significances of geometry, casting direction, size of specimens, and triggering materials contents on the measured ASR behavior were investigated. The study was able to highlight the correlations between the various tested parameters. Moreover, results revealed that the cylindrical specimens exhibited a higher expansion than that of the prismatic specimens by about 9−40%. Vertically cast specimens exhibited an increase in expansion over the others cast horizontally in the range from 3% to 9% based on measuring time. Moreover, increasing the volume of specimens lowered the expansion. Adding Fused silica reveals a higher increase in expansion in the mortar and concrete specimens than that with reactive aggregate only. However, the properties of Fused silica will differ the optimum percentage. The findings of this study emphasize various parameters that engineers need to consider while dealing with ASR results.